EFEKTIVITAS MODEL PEMBELAJARAN MIND MAPPING MENGGUNAKAN ALAT PERAGA TERHADAP HASIL BELAJAR MATEMATIKA - Khasanah, Binti Anisaul (JURNAL e-DuMath, 2017)
The learning model which is applied by the teacher, so far, was assumed uneffective in increasing studentsâ learning achievement, especially, on the subject of counting wide trapezium and kite. One of effort to overcome this problem was using mind mapping learning model with teaching media. This learning model asked the students to make or create their own two dimentional figure. the objective of the research wasÂ Â to know the effectivity of mind mapping learning model using teaching media on the students of fifth grade SD Negeri 4 Watuagung. The population of the research was all of the students at fifth grade SD Negeri 4 Watuagung at the first semester in the academic year of 2015-2016. The number of the students were 30 students.Based on the result of the research, it can be concluded that mind mapping learning model using teachingÂ media was able to make the learning process be more effective andÂ the students learning achievement which is involved the prosentage of teacherâs ability in the learning process 77.06%, studentsâ activity 78.81%, studentsâ response 76.25%, and if it was seen from studentsâ achievement based onÂ KKM 80.00%.